Analysis of differential efficacy of neurofeedback and biofeedback intervention on soccer performance - Hassan, Nik Muhammad Nazrin Bin Nik (Universiti Sains Malaysia, 2014)
The present study was undertaken with an objective to determine differential efficacy of psychotherapeutic interventions, namely Electromyographic (EMG) Biofeedback and Heart Rate (HR) Biofeedback in enhancing soccer skill ability in young male soccer players. Thirty six male soccer players from Universiti Sains Malaysia in the age ranging from 18 to 24 years volunteered as participants, who were assessed with psychological measure, such as, State-Trait Anxiety Inventory (SI Al); psychomotor parameter, such as. Reaction Time (RT), Mirror Drawing, Two Arm Coordination, Neuromuscular Steadiness; and psychophysiological variables, such as. Galvanic Skin Resistance (GSR), Heart Rate and Electromyoghaphy (EMG). Theses assessments were done for the screening test and pre-intervention base line information. Thereafter they were randomly and equally categorized into three groups, i.e.. each group consisted of 12 participants; viz. - Group A- control group; Group B - participants received training of EMG biofeedback and Group C — those who received HR Biofeedback training. Group wise respective intervention trainings (EMG & HR biofeedback) were imparted for 12 sessions (20 min.s /day; 2 days/ week for 6 weeks). Participants of Group A didn’t receive any intervention training. Mid-term analyses on all of the variables assessed in the pre-intervention phase were done on all of the participants after the completion of three weeks of intervention. Thereafter the similar protocol of intervention was followed for three more weeks. Thereafter all of the participants were assessed once again for the post-intervention analyses (following similar analyses protocols). Findings of the analyses suggested that both EMG and HR biofeedback intervention had beneficial impacts onto coordination and psychomotor abilities of the soccer players. Furthermore, both of the interventions have been observed to result in alteration in the psychobiological make-up of the participants, which together with the enhanced coordination and psychomotor abilities finally resulted in improvements in soccer shooting and agility skills performance.